Inferring surface water equilibrium calcite δ18O during the last deglacial period from benthic foraminiferal records: Implications for ocean circulation. (12th November 2015) - Amrhein, Daniel E.; Gebbie, Geoffrey; Marchal, Olivier; Wunsch, Carl
Abstract: The ocean circulation modifies mixed layer (ML) tracer signals as they are communicated to the deep ocean by advection and mixing. We develop and apply a procedure for using tracer signals observed "upstream" (by planktonic foraminifera) and "downstream" (by benthic foraminifera) to constrain how tracer signals are modified by the intervening circulation and, by extension, to constrain properties of that circulation. A history of ML equilibrium calcite δ 18 O ( δ 18 O c ) spanning the last deglaciation is inferred from a least‐squares fit of eight benthic foraminiferal δ 18 O c records to Green's function estimated for the modern ocean circulation. Disagreements between this history and the ML history implied by planktonic records would indicate deviations from the modern circulation. No deviations are diagnosed because the two estimates of ML δ 18 O c agree within their uncertainties, but we suggest data collection and modeling procedures useful for inferring circulation changes in future studies. Uncertainties of benthic‐derived ML δ 18 O c are lowest in the high‐latitude regions chiefly responsible for ventilating the deep ocean; additional high‐resolution planktonic records constraining these regions are of particular utility. Benthic records from the Southern Ocean, where data are sparse, appear to have the most power to reduce uncertainties in benthic‐derived ML δ 18 O c . Understanding the spatiotemporal covariance of deglacial ML δ 18 O c will also improve abilities of δ 18 O c records to constrain deglacial circulation. Key Points: Inverse methods quantify information about past circulations from tracer proxies Benthic tracer records constrain surface properties where deep water is formed A set of oxygen isotope records does not diagnose deglacial circulation changes